Virus-induced gene silencing of putative Diuraphis noxia (Kurdjumov) resistance genes in wheat - Starkus, Laura (Kansas State University, 2010)
The Russian wheat aphid Diuraphis noxia (Kurdjumov) is a serious pest of world cereal grain crops, primarily barley and wheat. A phenotypic characteristic of D. noxia feeding, leaf rolling, creates a leaf pseudo gall which protects aphids, making it difficult to treat infested plants with insecticides or biological control agents. Therefore, the use of D. noxia-resistant crops is a desirable aphid management tactic. Because of the development of virulent D. noxia biotypes, the identification of new sources of barley and wheat resistance is necessary. Virus-induced gene silencing (VIGS) utilizes the plant defense system to silence viruses in inoculated plants. The accumulation of virus RNA in plants triggers the defense system to silence sequences homologous to the introduced virus and sequences of interest from a plant are inserted into the virus and silenced along with the virus. The VIGS method was tested to determine the ability of barley stripe mosaic virus (BSMV) to serve as a VIGS vector in wheat plants containing the Dnx gene for resistance to D. noxia. Dnx leaves with silenced BSMV virus yielded D. noxia populations that were significantly no different from populations produced on healthy Dnx leaves. Thus, BSMV silencing does not interfere with Dnx resistance. Several different methods were examined to determine how best to confine aphids to the silenced leaf, and a modified plastic straw cage was chosen as the optimum cage type. Microarray and gene expression data were analyzed to select two NBS-LRR type disease resistance protein genes - TaAffx.104814.1.S1_at and TaAffx.28897.1.S1 - (NBS-LRR1 and NBSLRR2), in order to assess their role in Dnx resistance. NBS-LRR1 and NBSLRR2 were silenced by inoculating leaves of Dnx plants with barley stripe mosaic virus (BSMV) containing sequences of each gene. Controls included Dnx and Dn0 plants inoculated with BSMV and non-BSMV inoculated plants. Aphids were allowed to feed on control and treatment plants to assess aphid population and mean weight of aphids surviving at the end of the experiment. There were no differences among treatments based on aphid population, but there were significant differences the mean weights of aphids reared on several different treatments.
Keywords: Virus induced gene silencing (VIGS); Russian wheat aphid; Diuraphis noxia; Cereal grains; Plant-insect interactions; Barley stripe mosaic virus (BSMV); Agriculture, Agronomy (0285)